Simulating Poor Visibility Conditions Using Image Processing - Rokita, Przemyslaw (Real-time imaging, 1997)
Image processing is usually associated with pattern recognition and is rather treated as a subject outside of the computer graphics interest. Basically, computer graphics algorithms are used for the visualization of scenes or models described using some abstract notation, while image processing is used in the opposite way – i.e. when finding an abstract description of the analysed pattern. This paper proposes to use the image processing approach for rendering optical effects in computer graphics algorithms. Efficient techniques for rendering various weather conditions are very important for the development of flight and driving simulators. Under heavy rain drivers and pilots are very disturbed by the raindrops and the water film falling on the windshield. This paper proposes an efficient technique for rendering optical effects caused by the rain on the windshield, by adaptive iterative picture filtering. The advantage of the image processing algorithm described in this paper is that it can be easily implemented in a pipeline. The extensions based on the proposed algorithm can be added to the existing rendering systems as final stages of the visualization pipeline. Proposed algorithm can be used for the real-time generation of realistic and artistic optical effects in, for example, visual simulators, virtual reality and multi-media applications.